Análise comparativa de sequências completas de genomas de cloroplasto de Pterodon emarginatus e Pterodon pubescens (Leguminosae) - Freitas, Juliana Borges Pereira Brito (2021)
FREITAS, J. B. P. B. Comparative analysis of complete chloroplast genome sequences of Pterodon emarginatus and P. pubescens (Leguminosae). 2020. Dissertation (Master in Genetics and Plant Breeding) – School of Agronomy, Federal University of Goiás, Goiânia, 2020.¹ The chloroplast is a cellular organelle that has its own genome. Several projects of chloroplast genome sequencing have been developed with species of the legume group, family to which the species Pterodon emarginatus and P. pubescens belong. These two species of the genus Pterodon are native to the Cerrado biome, are popularly known as sucupira branca or faveira, and have potential for medicinal use and lumber. The present work aimed to know and compare the structure and organization of the chloroplastidial genomes of P. emarginatus and P. pubescens, in order to collaborate with the knowledge about the phylogenetic relationships between these species. Sequencing was performed using the Illumina MiSeq platform. The genomes were assembled using a de novo strategy associated with reference genome guided assembly. Annotation of genes and repetitive regions of the genomes was performed. In addition, nucleotide diversity was estimated and phylogenetic relationships of these species with other species of the Leguminosae family, whose chloroplastid genomes are available in databases, were analyzed. These diversity and phylogeny analyses were performed based on the gene sequences of the chloroplastidial genomes. The complete sequence of the chloroplastidial genome of P. emarginatus is 159,823 bp, while that of P. pubescens is 159,818 bp. Both genomes have a quadripartite structure, composed of two inverted regions (IR) with 25,584 bp in both species, separated by a short single copy region (SSC), with 19,359 bp and 19,367 bp, respectively, for P. pubescens and P. emarginatus and a long single copy region (LSC), with 89,291 bp in P. pubescens and 89,288 bp in P. emarginatus. A total of 127 genes were predicted in the chloroplast genome in both species, among which, 109 single copy genes and 18 duplicated genes in the inverted regions. A total of 143 microsatellite regions were identified in P. emarginatus and 141 in P. pubescens. The gene content was similar to that of other chloroplastidial genomes of legume species, with an emphasis on similarity with Dipteryx alata and Styphnolobium japonicum, with few exceptions of gene losses and gains. Nucleotide diversity estimates of gene regions were 0.062 in LSC, 0.076 in SSC, and 0.036 in IR. Phylogenetic analysis demonstrated the proximity between the genera Pterodon and Dipteryx, both from the clade Dipterygeae as well as the close relationship between the clades ADA and Cladrastis. The genetic information obtained on the chloroplastidial genomes of P. emarginatus and P. pubescens in this study reinforces the similarity and evolutionary proximity between these species. These results may contribute to other studies, such as molecular systematics and population genetics and phylogeography.